Economic aspects of institutional transformation in post-Soviet countries – current state and consequences for their development and competitiveness (Economic and Political Thought, 2017)
The subject of this article is the problem of institutional transformation,specifically its economic aspects, in countries of the former USSR. First,selected theoretical aspects related to institutional transformation ofpost-communist economies are discussed. Then, a synthetic analysis ofthe advancement of this transformation in the post-Soviet area and of itsconsequences for the development and international competitiveness of theireconomies is conducted. And finally, reference is made to the future ofinstitutional transformation of post-Soviet economies. The analysis showsthat: from the very beginning (i.e. the break-up of the USSR), the processesof institutional transformation of post-Soviet economies have been stronglydifferentiated both in terms of adopted transformational strategies and theireffectiveness, as evidenced by the very different results observed presentlyin this regard; the current level of development, as well as internationalcompetitiveness of most post-Soviet economies are not a direct consequenceof the advancement of their institutional transformation; completion ofthe processes of institutional transformation is not to be expected in theforeseeable future and neither is the introduction of a liberal institutionalenvironment typical for free market economies.